Patient preferences for prenatal testing and termination of pregnancy for congenital anomalies and genetic diseases in Ethiopia. (18th June 2019) - Brooks, Daniel; Asta, Katharine; Sturza, Julie; Kebede, Birhanu; Bekele, Delayehu; Nigatu, Balkachew; Hewison, Jenny; Quinonez, Shane C.
Abstract: Objective: As prenatal diagnostic services expand throughout low‐income countries, an important consideration is the appropriateness of these services for patients. In these countries, services now include prenatal ultrasound and occasionally genetic testing. To assess patient interest, we surveyed pregnant patients at a hospital in Addis Ababa, Ethiopia, on their preferences for prenatal testing and termination of affected pregnancies for congenital anomalies and genetic diseases. Method: One hundred one pregnant patients were surveyed on their preferences for prenatal testing and termination of affected pregnancies using a survey covering various congenital anomalies and genetic diseases. Results: Eighty‐nine percent of patients reported interest in testing for all conditions. Three percent of patients were not interested in any testing. Over 60% of patients reported interest in termination for anencephaly, early infant death, severe intellectual disability, hemoglobinopathy, and amelia. Patients were more likely to express interest in prenatal testing and termination for conditions associated with a shortened lifespan. Conclusion: Ethiopian patients were interested in prenatal testing and termination of pregnancy for many conditions. Advancing prenatal diagnostic capacities is a potential strategy for addressing the incidence of congenital anomalies and genetic disease in Ethiopia. Importantly, there exist many factors and technological limitations to consider before implementation. Abstract : What's already known about this topic? Prenatal genetic services are expanding throughout many low‐ and middle‐income countries. In low‐ and middle‐income countries, little is known on patient preferences for prenatal testing for congenital anomalies and genetic diseases and patient interest in termination of affected pregnancies. What does this study add? Patients at St. Paul's Hospital in Addis Ababa, Ethiopia, were interested in prenatal testing and termination of pregnancy for many congenital anomalies and genetic diseases. Studying patient preferences for genetic services in a low‐income country is possible and should be considered prior to the introduction of a new service and/or technology.